2017
DOI: 10.1080/16549716.2017.1290426
|View full text |Cite
|
Sign up to set email alerts
|

Physical partner violence, women’s economic status and help-seeking behaviour in Dar es Salaam and Mbeya, Tanzania

Abstract: Background: Women’s responses to partner violence are influenced by a complex constellation of factors including: psychological attachment to the partner; context of the abuse; and structural factors, all of which shape available options for women outside of the relationship. Objective: To describe women’s responses to physical partner violence; and to understand the role of women’s economic resources on their responses. Methods: Cross-sectional data from Dar es Salaam and Mbeya, Tanzania. Multivariate logisti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
14
0
9

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 27 publications
3
14
0
9
Order By: Relevance
“…In such conditions, women regularly fail to disclose to others to sought assistance. This finding is in line with the different studies done in Tanzania [29] and Dhaka slum [26].…”
supporting
confidence: 92%
“…In such conditions, women regularly fail to disclose to others to sought assistance. This finding is in line with the different studies done in Tanzania [29] and Dhaka slum [26].…”
supporting
confidence: 92%
“…However, previous studies show that men are more likely than women to express unwillingness or lack of motivation to seek help for stressful life events [ 42 , 43 ]. The finding of this paper may be attributed to contextual factors such as women’s lack of autonomy and economic empowerment as well as low levels of education compared to men [ 25 27 ]. The proportion of women with no education was more than twice higher than that of men (73% and 34% respectively).…”
Section: Discussionmentioning
confidence: 99%
“…Education has also been shown to be positively associated with a favorable attitude towards seeking help for SGBV. The impact of education is mainly through increased awareness, autonomy and economic empowerment among those with high levels of education [ 25 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…Regional wise, there is a close correlation between the prevalence of IPV victimization and child morbidity; regions with high prevalence of IPV victimization also have reported high rates of child morbidity and mortality [ 5 , 25 – 28 ]. In Tanzania, recent studies indicated that the prevalence of IPV victimization range between 15 to 78% [ 29 – 33 ] while under-five mortality rate is 67 deaths per 1,000 live births [ 33 ], comparatively higher than the global statistics [ 11 , 34 ]. Therefore, exposure to IPV victimization might have a direct or indirect association with child mortality [ 35 , 36 ] or rather morbidity that could lead to mortality [ 24 , 37 , 38 ].…”
Section: Introductionmentioning
confidence: 99%